Reassessment of Robert Menzies' contribution in the Engineers Case - Carney, Gerard (Lawbook Co., 2015)
The recent discovery of Sir Robert Menzies' handwritten notes made for and during his appearance as counsel in the Engineers' Case in 1920 provides a unique insight into the six days of that hearing, of which no transcript exists. They also allow a reassessment of his role as a young 25-year-old barrister, opposed by a formidable line-up of counsel representing the States. This article attempts to piece together the line of argument each day, as well as something of the atmosphere in the High Court and the personalities of the other counsel.